Discrete breather clusters in strained graphene - Zhou, Kun (2013)
Molecular-dynamics simulations based on many-body interatomic potentials are conducted to investigate the clusters of discrete breathers in graphene under in-plane homogeneous strain. It is found that the discrete breather clusters can easily be excited when the gap in the phonon density of states is introduced by the homogeneous strain. Clusters of up to four discrete breathers were studied. We demonstrate that such clusters are robust with respect to small perturbations and can have the lifetime of order of 103 oscillation periods. Partial energy exchange between discrete breathers in the clusters was observed under certain conditions. The possible role of discrete breather clusters in formation of lattice defects is discussed.